Study of the Effect of the Coupling in a Dispersion-managed Dual Core Optical Fiber Using the Collective Variables Approach - Djob, Roger Bertin; Kenfack-Jiotsa, Aurélien; Kofané, Timoléon Crépin (Journal of Applied Nonlinear Dynamics, 2026)
This paper highlights the interaction between two gaussian pulses propagating inside a dual core optical fiber by the mean of collective variables (CVs) approach. The main result is that energies of the signals being propagated in such fiber with linear coupling always end up being compensated whatever their amplitudes at the entry. It also appears convergence or divergence of the temporal positions of the neighboring solitary waves.